PENGARUH GAYA KEPEMIMPINAN TRANSFORMASIONAL DAN MOTIVASI KERJA TERHADAP KINERJA GURU MELALUI KEPUASAN KERJA GURU SMK YP 17 SELOREJO KABUPATEN BLITAR - Widyanto, Sutaji (Magister Manajemen Universitas Wisnuwardhana, 2021)
Trainner position of teachers as a vocational school in particular, have a role to organize, organize, direct and train to utilize all its resources both from private teachers themselves and from school in order to achieve the goals set. The performance of teachers in an educational institution is an interesting factor to be investigated.Based on data analysis found that transformational leadership style and work motivation influence on job satisfaction and teacher performance. Job satisfaction affect the performance of teachers. Job satisfaction mediates the effect of transformational leadership style and work motivation on teacher performance.In order to improve the performance of teachers, the leadership of SMK YP 17 Selorejo Blitar should use a charisma so that every action has the allure and should be followed, as well as exemplary, the leadership is able to inspire and keluasaan insights, leaders have a vision of the future and based intellectual. In addition it must pay attention to the need for achievement, need for affiliation and need for power